Health literacy in diabetes: psychometric properties of a new scale and effect on biochemical parameters (Research, Society and Development, 2022)
This study evaluated the health literacy (HL) competencies (access, understand/appraise and apply) using a new developed scale and the association with biochemical profile among people living with diabetes. For the diagnosis of diabetes, biochemical parameters were used. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) estimated the construct validity of the scale. Statistical models estimated the association of HL with socioeconomic, biochemical, anthropometric and cognitive parameters. This study included 341 people living with diabetes. The results showed that 91.9% received information related to diabetes. EFA demonstrated a proper factorial fit (KMO = 0.919) and the items were loaded in three factors: access, understand/appraise and apply. CFA confirmed the fit of the model (l²/df of 2.09; RMSEA of 0.061). High levels of access to information related to diabetes led to a higher apply level self-reported. However, a high apply level was not associated with better biochemical profile (p < 0.05), including the dosage of glycated hemoglobin. Moreover, regression models showed that some characteristics were associated with high HL in all its domains, such as skin color and cognitive condition. Furthermore, a higher proportion of men had high access to information related to diabetes, compared to women. These results show that different factors must be considered in the HL process to achieve proper self-management behavior to control the disease or prevent its complications. Health information for people living with diabetes should focus on specific risk factors or behaviors that modulate biochemical parameters.